Impact of Early Marriage on Adolescent Reproductive Health - Fitria Lestari; Imas Nurjanah (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Early Marriage Is A Case That Still Occurs In Indonesia. Marriage is an inner and outer bond between men and women who want to continue their descendants and have a family. The number of Class XII MA Darul Ihsan students who married at school age during the 2021/2022 academic year totaled 2 people, in 2020/2021 there were 0 cases, and in 2019/2020 there were 5 people. To Develop Knowledge About the Impact of Early Marriage on Adolescent Reproductive Health at MA Darul Ihsan. Pre-experimental research was carried out on Darul Ihsan MA students with 47 respondents taking a sample, in order to obtain research results using T-test analysis on pretest and post-test with P Value <0.001. Results of Statistic Test Calculations obtained using computerization, so that in Obtained a T-value of 8.609 and P = 0.001 (P<0.001), which means that there is an effect of education on the impact of early marriage on adolescent reproductive health. This Education on the Impact of Early Marriage on Reproductive Health can have an influence on MA Darul Islam students who can be said to still have cases of early marriage, so they can develop the knowledge of students and students of Ma Darul Ihsan and apply that knowledge in their environment.